Inhibitory effect of HTLV‐1 infection on the production of B‐cell activating factors in established follicular dendritic cell‐like cells. Issue 3 (4th May 2021) - Takatani, Ayuko; Nakamura, Hideki; Furukawa, Kaori; Endo, Yushiro; Umeda, Masataka; Shimizu, Toshimasa; Nishihata, Shin‐ya; Kitaoka, Kyoko; Nakamura, Tatsufumi; Kawakami, Atsushi
Abstract: Introduction: The low frequency of ectopic germinal center in labial salivary glands of patients with human T‐cell leukemia virus type 1 (HTLV‐1) antibody‐positive Sjögren's syndrome (SS) suggests that HTLV‐1 has some effects on follicular dendritic cells (FDCs). Methods: We used flow cytometry, immunofluorescence, and enzyme‐linked immunosorbent assays (ELISAs) to investigate the direct effect of HTLV‐1 on B‐cell activating factors produced by established FDC like cells obtained from excised human tonsils. We then measured the serum B‐cell activating factor (BAFF) and C‐X‐C motif ligand (CXCL) 13 concentrations of the HTLV‐1‐seropositive SS patients and the HTLV‐1‐seronegative SS patients by ELISA. Results: Among the 31 isolated specimens, 22 showed morphological characteristics of FDCs. Day 2‐cultured specimens showed expressions of CD14, CD23, CD40, intracellular adhesion molecule‐1 (ICAM‐1), and vascular cell adhesion molecule‐1. After 2 weeks, 12 of these specimens expressed ICAM‐1, FDC, and fibroblast cell marker. Intracellular BAFF and CXCL13 were constitutively expressed regardless of stimulation. After direct coculture with the HTLV‐1‐infected T‐cell line HCT‐5 or MT‐2, the BAFF and CXCL13 expressions on the FDC‐like cells were decreased in accord with the increased number of HCT‐5 and MT‐2 cells with styliform change and without HTLV‐1 Gag protein expression. Interferons upregulated the concentration of BAFF (but not CXCL13) in the culture supernatant, which showed a declining trend under the presence of HCT‐5 or MT‐2. The serum concentrations of BAFF and CXCL13 in the HTLV‐1‐seropositive SS patients were lower than those of the HTLV‐1 seronegative SS patients. Conclusions: HTLV‐1 partially inhibited the BAFF and CXCL13 expressions of established FDC‐like cells. Graphical abstract: Expression of B‐cell activating factor (BAFF) was upregulated by addition of interferons. Although BAFF expression was inhibited by addition of human T‐cell leukemia virus type 1 infected cell line, HCT‐5 and MT‐2, the level was not inhibited by addition of control cell line, MOLT‐4.